"The end of Roe means the end of bodily autonomy": reproductive technologies and temporal framing of women's agency post-Dobbs - Hasberger, Hayley, author; Dunn, Tom, advisor; Gibson, Katie, committee member; Martey, Rosa Mikeal, committee member (Colorado State University. Libraries, 2023)
On June 24th, 2022, the U.S. Supreme Court issued its ruling in the case of Dobbs v. Jackson Women's Health Organization and overturned Roe v. Wade, an almost half century old landmark decision in support of women's reproductive rights. My analysis responds to the exigence of the current technological and post-Dobbs moment, to highlight the discursive implications of a nationwide reproductive technology decision. This thesis examines Jezebel's media framing of reproductive technologies, arguing that women-centric discourses of reproductive technologies post-Dobbs center temporality as a major theme in two distinct ways: 1) by demonstrating the realness of the present moment and 2) pointing to dystopic visions of America's coming future. I contend that these two parallel themes in the discourse frame differing paths towards women's agency, which can have a meaningful impact on the material actions women take in reality. As the overturning of Roe v. Wade continues to unfold, it will be paramount to continue to research and explore communication outcomes associated with the relationship between reproductive technologies and women's bodily autonomy.
The end of Roe means the end of bodily autonomy: reproductive technologies and temporal framing of women's agency post-Dobbs
Keywords: bodily autonomy; reproductive technology; abortion; temporal rhetoric; Dobbs